Management of Early Childhood Education Program at PAUD Nurul Hikmah Suryalaya Post Lengkong Bandung - Khotimah, Iim; Lesmi, Kirana; Takiah, Sofiatu (Jurnal Edusci, 2024)
The title of this work is Management of Early Childhood Education Programs at PAUD Nurul Hikmah Suryalaya Bandung Post. The study began with observations on well-organized and orderly leadership at the Nurul Hikmah Suryalaya Bandung PAUD Post. This study explores information on the management of well-organized education programs at the Nurul Hikmah PAUD Post. What are the inhibiting supporting factors? This study used a qualitative descriptive method. Data collection, observation, interview, and documentation techniques: data analysis techniques, acquisition, reduction, presentation, and reasoning. The results of this study found that the answers about the Management of PAUD Nurul Hikmah Suryalaya Bandung Post were well organized due to supporting factors from the surrounding community, PKK, Yandu Post, and school residents. The external supporting factors include cooperation with PAUD Post partners. In the management of early childhood education at the Nurul Hikmah PAUD Post, there is also an inhibiting factor, namely the parents' lack of attention to their children. Program delays are due to conflicts with programs of other educational institutions at the same time. Efforts to overcome existing obstacles include communicating and contacting the parents of students. Meanwhile, late programs can be overcome by replacing them on another day or time. The flagship program of PAUD Nurul Hikmah Post is an extracurricular program that includes dance, pencak silat, and painting. Meanwhile, religious lessons have always been part of the daily education program, including memorizing short letters, daily prayers, and Asmaul Husna and Dhuha prayers.